Production of 1,3-propanediol by Clostridium butyricum VPI 3266 using a synthetic medium and raw glycerol - González-Pajuelo, M. (2004)
Growth inhibition of Clostridium butyricum VPI 3266 by raw glycerol, obtained from the biodiesel production process, was evaluated. C. butyricum presents the same tolerance to raw and to commercial glycerol, when both are of similar grade, i.e. above 87% (w/v). A 39% increase of growth inhibition was observed in the presence of 100 g l 1 of a lower grade raw glycerol (65% w/v). Furthermore, 1,3-propanediol production from two raw glycerol types (65% w/v and 92% w/v), without any prior purification, was observed in batch and continuous cultures, on a synthetic medium. No significant differences were found in C. butyricum fermentation patterns on raw and commercial glycerol as the sole carbon source. In every case, 1,3-propanediol yield was around 0.60 mol/mol glycerol consumed.